2014
DOI: 10.1099/mic.0.078329-0
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative production of short-chain fatty acids in Escherichia coli

Abstract: Escherichia coli was engineered for the production of even-and odd-chain fatty acids (FAs) by fermentation. Co-production of thiolase, hydroxybutyryl-CoA dehydrogenase, crotonase and trans-enoyl-CoA reductase from a synthetic operon allowed the production of butyrate, hexanoate and octanoate. Elimination of native fermentation pathways by genetic deletion (DldhA, DadhE, DackA, Dpta, DfrdC) helped eliminate undesired by-products and increase product yields. Initial butyrate production rates were high (0.7 g l "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…After further screening of TEs, the engineered strain, which was expressed TE Fs2108, produced 1,425 mg/L of valerate (McMahon and Prather, ). Volker et al () introduced propionyl‐ CoA synthesis pathway into engineered strain combined with the thiolase, hydroxybutyryl‐CoA dehydrogenase, crotonase, and trans‐enoyl‐CoA reductase. The resulting strain BE1952 accumulated 200 mg/L of valerate and 8 mg/L of enanthate under fermentative condition.…”
Section: Resultsmentioning
confidence: 99%
“…After further screening of TEs, the engineered strain, which was expressed TE Fs2108, produced 1,425 mg/L of valerate (McMahon and Prather, ). Volker et al () introduced propionyl‐ CoA synthesis pathway into engineered strain combined with the thiolase, hydroxybutyryl‐CoA dehydrogenase, crotonase, and trans‐enoyl‐CoA reductase. The resulting strain BE1952 accumulated 200 mg/L of valerate and 8 mg/L of enanthate under fermentative condition.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CoA-dependent reverse β-oxidation also enables the production of odd-chain alcohols, as acetyl-CoA can be condensed with propionyl-CoA if a source of propionate is available 112 . Propionyl-CoA can be synthesized through ketobutyrate 113,114 , which is a metabolite downstream of the threonine biosynthesis pathway, or through the 1,2-propandiol pathway 115 . However, the production of odd-chain alcohols loses redox potential, which results in lower yields, unless properly balanced by pairing a redox-deficient pathway with a redox-surplus pathway 114 , whereas the production of even-chain alcohols from carbohydrates is redox balanced.…”
Section: Coa-dependent Reverse β-Oxidationmentioning
confidence: 99%
“…However, the reported titer of butyric acid in batch fermentations by these E. coli derivatives was ≤10 g.L -1 compared to Clostridium spp. (highest titer of about 45 g.L -1 in batch fermentations) (Vandak et al, 1995;Volker et al, 2014) with one study reporting as high as 62.5 g.L -1 using C. tyrobutyricum (Song et al, 2010). Although a mutant strain of C. acetobutylicum produced very low level of acetate and lactate as co-products during the butyrate production phase, the butyrate titer and yield of 32.5 g.L -1 and 0.39 g.g -1 (theoretical yield of butyrate from glucose is 0.49 g.g -1 ), respectively (Jang et al, 2014), are lower than the reported values for C. butyricum and C. tyrobutyricum listed above.…”
Section: Introductionmentioning
confidence: 99%